New Directions for Clarinet - Rehfeldt, Phillip (USA Scarecrow Press, 1994)
Phillip Rehfeldt has assembled here techniques of dealing with clarinet performances as they have evolved since 1950. He catalogs contemporary practices that differ from those formerly standardized, provides perspective on performance capabilities and limitations, and includes suggestions for performance based on his own experience.The new edition has been completely rewritten, corrected where necessary, and updated. Rehfeldt has added the complete list of William O. Smith's clarinet compositions and recordings to the previous listing of his early multiphonic fingerings. The new edition also includes an appendix containing Eric Mandat's quarter-tone fingerings; a second, extensive music bibliography, the "International Update"; and an updated and annotated bibliography of music literature.
Keywords: Clarinet; Method